Psoriasis and Risk of Uveitis: A Systematic Review and Meta-Analysis - Chayada Chaiyabutr (2020)
Copyright © 2020 Chayada Chaiyabutr et al. Background: Uveitis is a known ophthalmologic manifestation of seronegative spondyloarthropathy, including psoriatic arthritis. However, the data is less clear among patients with psoriasis due to the limited number of published studies. Aims: To investigate whether the risk of incident and prevalent uveitis is elevated among patients with psoriasis using systematic review and meta-analysis technique. Methods: The MEDLINE and EMBASE databases were searched from their inception to May 2019. Eligible studies must have included a psoriasis group and a nonpsoriasis group. Eligible studies must also have investigated for prevalent or incident uveitis, and the magnitude of difference between the study groups must have been reported. Pooled risk ratio and 95% confidence interval (CI) were calculated using random-effect generic inverse variance methods. Results: Of 7,107 potentially eligible articles from the EMBASE and MEDLINE databases, 7 studies were included in the meta-analysis. Two of those studies compared the incidence, and 5 studies compared the prevalence of uveitis between the psoriasis and nonpsoriasis groups. For incident uveitis, a total of 5,865,801 patients (222,083 with psoriasis and 5,643,718 without psoriasis) were analyzed. For prevalent uveitis, a total of 1,343,436 patients (37,891 with psoriasis and 1,305,545 without psoriasis) were studied. The risk of incident uveitis was significantly higher among patients with psoriasis with a pooled risk ratio of 1.23 (95% CI: 1.05-1.45, I2 = 55%). The risk of prevalent uveitis was also significantly higher among patients with psoriasis with a pooled risk ratio of 1.97 (95% CI: 1.68-2.31, I2 = 0%). Conclusions: The results of this study revealed significantly increased risk of both prevalent and incident uveitis among patients with psoriasis.